2018
DOI: 10.1002/chem.201800947
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Electron Transfer of Stacked Heterodimers of Perylene Diimide Derivatives in a DNA Duplex

Abstract: The preparation of homo- and heterocomplexes composed of the parent perylene diimide (PH) and pyrrolidine-substituted perylene diimide (PN) in DNA and rapid electron transfer in these complexes, which has been analyzed by steady-state fluorescence and femtosecond transient absorption measurements, have been demonstrated. The DNA molecules possessing PH and PN were prepared through a recently developed method that involved the reaction of enzymatically generated abasic sites with the amino groups of the perylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…3). 25 The morphologies of the resins. The difference of crystallinity of PODSA-MM resins before and aer introducing side group were investigated by X-ray diffraction (XRD) analysis at the range of 5 -50 .…”
Section: Synthesis and Characterization Of The Resinsmentioning
confidence: 99%
“…3). 25 The morphologies of the resins. The difference of crystallinity of PODSA-MM resins before and aer introducing side group were investigated by X-ray diffraction (XRD) analysis at the range of 5 -50 .…”
Section: Synthesis and Characterization Of The Resinsmentioning
confidence: 99%
“…The covalent incorporation of TO molecules into DNA was achieved through the reductive amination at abasic sites generated by an enzymatic reaction based on our previous method (Figure 1, Table 1). [59,60] We have demonstrated that the abasic sites can work as both binding pockets for the hydrophobic dyes and reactive sites for the conjugation, allowing DNA modification at a specific site and efficient multiple incorporation of functional molecules. [59,60] We utilized our strategy for the preparation of the TO-conjugated DNA.…”
Section: Preparation Of To-conjugated Dna By Reductive Amination At Abasic (Ap) Sitesmentioning
confidence: 99%
“…[59,60] We have demonstrated that the abasic sites can work as both binding pockets for the hydrophobic dyes and reactive sites for the conjugation, allowing DNA modification at a specific site and efficient multiple incorporation of functional molecules. [59,60] We utilized our strategy for the preparation of the TO-conjugated DNA. The modification of TO was carried out according to the scheme shown in Figure 1b.…”
Section: Preparation Of To-conjugated Dna By Reductive Amination At Abasic (Ap) Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular structures based on the perylene bisimide (PBI) chromophore have been the object of extensive studies both from the perspective of fundamental photophysical properties, for instance, high emission yield 1,2 , energy transfer 3,4,5 , electron transfer 6,7 and singlet fission 8,9 , as well as from the perspective of potential application in optoelectronic devices, such as optical sensors 10,11 , solar light collectors 12,13 and optical power limiters 14 . Recently, properties of PBI aggregates have begun to be explored 15,16,17 .…”
Section: Introductionmentioning
confidence: 99%